2014
DOI: 10.14233/ajchem.2014.17809
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Manganese, Iron, Zinc, Copper and Nickel in Tilapia and Cyprinus carpio Fish Consumed in Syria by Flame Atomic Absorption Spectrometry

Abstract: The present work describes a microwave digestion procedure by using new convenient digestion mixture (nitric acid and hydrogen peroxide) to determine manganese, zinc, copper, iron and nickel in (Tilapia and Cyprinus carpio) fish samples, breeding in artificial lakes, employing flame atomic absorption spectrometry. The optimization conditions involving the factors: amount of fish, microwave power and power time were studied. The experiments of this factorial were carried out using two species of local fish whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Brzezicha-Cirocka et al [18] reported extraction levels of 32.9 ± 12.4% for black tea and 29 ± 5.3% for green one which points out that there is no significant difference between these two types of tea. According to Antakli et al [21], however, the extraction levels were significantly different, although the number of samples tested in that work was very low (27% and 11-18% for black and green tea, respectively; N = 3) so it's difficult to draw a clear conclusion.…”
Section: Manganese In the Samplesmentioning
confidence: 83%
“…Brzezicha-Cirocka et al [18] reported extraction levels of 32.9 ± 12.4% for black tea and 29 ± 5.3% for green one which points out that there is no significant difference between these two types of tea. According to Antakli et al [21], however, the extraction levels were significantly different, although the number of samples tested in that work was very low (27% and 11-18% for black and green tea, respectively; N = 3) so it's difficult to draw a clear conclusion.…”
Section: Manganese In the Samplesmentioning
confidence: 83%